Does Inflation in China Affect the United States and Japan? - Willard, Luke (IMF Working Papers; Working Paper ;, 2006)
With China's share in global trade increasing rapidly, some argued in 2002-03 that China was exporting deflation to other countries as it was dumping cheap goods in mature markets. Later, others argued that China was sucking in commodities and thus causing sharp increases in global prices. The theoretical literature so far has provided mixed conclusions regarding the strength of international transmission of inflation. This paper uses a number of econometric techniques to assess the extent of the link between inflation rates between China and the United States and Japan. It finds only limited empirical evidence at the aggregate level for consumer price inflation in China leading to price changes in the United States and Japan. However, it finds some evidence that inflation in the United States has an impact on Chinese inflation, consistent with the literature that argues that inflation is propagated from the reserve currency economy to other economies. In either case, the impact is short lived. At a more disaggregate level, there appears to be stronger sector-specific linkages between prices in China and in the United States and Japan, both for food and at the household level for manufactured goods.